Social entrepreneurship in Kenya: understanding models, drivers, constraints and opportunities for enhanced impact in healthcare - Chater, Rachel (Research of GSB, 2018)
Social entrepreneurship is a rising field, gaining momentum and recognition. With the impact it is already having plus its substantial scope for further growth and influence, it is important to understand the dynamics that drive and affect it as well as the ecosystem it sits within. At present, there is very limited research available on social entrepreneurship in a developing country setting and even less on its application within the health sector. Hence, the purpose of this study is to understand the objectives, operations, and challenges of social enterprises in Kenya, with a specific focus on the health sector. As an exploratory study, an open, grounded theory, qualitative approach was adopted to allow the generation of insight into this little understood context. This research presents a set of emerging themes and propositions that answers the primary research question: What drives and affects innovation among social enterprises in Kenya's health sector? Ultimately it provides a theoretical framework that addresses the core concern of establishing a social enterprise that has impact in a developing country's health sector. The themes that emerged from the data throughout the study support the following main conclusions: 1) The character, perspective and experience of the social entrepreneur(s) in combination with the identified needs (opportunities) drive innovation in Kenya's health sector and 2) Challenges, enablers and environmental influencers (infrastructure, regulatory/ political, support and operational) affect the operation and innovation of social enterprises in Kenya's health sector.